Combination therapy with rituximab, low-dose cyclophosphamide, and prednisone for idiopathic membranous nephropathy: a case series - Cortazar, Frank B. (BMC Nephrol, 2017)
BACKGROUND: Membranous nephropathy is a common cause of the nephrotic syndrome. Treatment with standard regimens fails to induce complete remission in most patients. We evaluated the efficacy of combination therapy with rituximab, low-dose, oral cyclophosphamide, and an accelerated prednisone taper (RCP) for the treatment of idiopathic membranous nephropathy. METHODS: We analyzed 15 consecutive patients with idiopathic membranous nephropathy treated with RCP at Massachusetts General Hospital. Seven patients (47%) received RCP as initial therapy, and the other eight patients (53%) received RCP for relapsing or refractory disease. All patients had at least 1 year of follow-up. The co-primary outcomes were attainment of partial and complete remission. Partial remission was defined as a urinary protein to creatinine ratio (UPCR) < 3 g/g and a 50% reduction from baseline. Complete remission was defined as a UPCR < 0.3 g/g. Secondary outcomes were serious adverse events and the change in proteinuria, serum creatinine, serum albumin, cholesterol, triglycerides, and immunoglobulin G levels after 1 year of treatment. RESULTS: Over a median follow-up time of 37 (IQR, 34–44) months, 100% of patients achieved partial remission and 93% of patients achieved complete remission at a median time of 2 and 13 months, respectively. After 1 year of treatment, median (IQR) UPCR declined from 8.2 (6.6–11.1) to 0.3 (0.2–0.7) g/g (P < 0.001). Three serious adverse events occurred over 51 patient years. No patients died or progressed to ESKD. CONCLUSIONS: Treatment of idiopathic membranous nephropathy with RCP resulted in high rates of complete remission. Larger studies evaluating this regimen are warranted. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12882-017-0459-z) contains supplementary material, which is available to authorized users.